THE ROLE OF PARTNERSHIP IN PRODUCTION TOWARDS PERFORMANCE OF INDONESIA'S MICRO AND SMALL ENTERPRISES - Vanessa Vicario; Catharina Badra Nawangpalupi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
A partnership can increase production capability due to the financial limitations of Micro and Small Enterprises (MSEs). Based on Indonesia’s Micro and Small Industry Profile 2018, partnerships in raw materials, machinery, facilities, infrastructure, and equipment as a partnership in production are the most widely implemented types of partnerships. However, research on partnerships in production is still very limited although it has been practically proven that partnerships in production can improve the performance of MSEs. The study aims to examine the role of partnership in production towards the performance of MSEs theoretically and propose recommendations for MSEs to improve their performance. The contribution of this study is the developed model of MSE’s performance in Indonesia which considers a partnership in production as a moderating variable. Also, consider process innovation and demand optimization as independent variables. This study uses the data of Micro and Small Industry Survey 2015 and examine the hypothesis using regression analysis. This study found there is a significant positive effect of interaction between demand optimization and partnership but a significant negative effect between a process innovation and partnership towards performance. The negative effect may occur temporally because there is time to adopt new production skills or techniques.